Relationships between finger-length ratios, ghrelin, leptin, IGF axis, and sex steroids in young male and female swimmers - Jürimäe, T.; Voracek, M.; Jürimäe, J.; Lätt, E.; Haljaste, K.; Saar, M.; Purge, P. (European Journal of Applied Physiology, 2008)
The aim of this study was to investigate possible relationships between different right-hand finger-length ratios and different fasting hormone concentrations in young swimmers. Fifty-five young swimmers participated in this study (26 boys and 29 girls, aged 10-17 years). The original method of Visnapuu and Jürimäe (J Strength Cond Res 21:923-929, 2007) was used for the measurement of length parameters of the hand. The following finger-length ratios were calculated: 1D:2D, 1D:3D, 1D:4D, 1D:5D, 2D:3D, 2D:4D, 2D:5D, 3D:4D, 3D:5D, and 4D:5D. All finger-length ratios were significantly higher in girls compared with boys. Ghrelin, leptin, testosterone in boys, estradiol in girls, insulin-like growth-factor I (IGF-I), IGFBP-3, and insulin were analyzed. Leptin and insulin concentrations were lower in boys compared with girls. In both groups, the relationships between finger-length ratios and basic anthropometric parameters were not significant. In girls, estradiol correlated negatively with 2D:3D (r = -0.51) and 2D:4D (r = -0.49) finger ratios. In boys, ghrelin concentration correlated with most of the finger-length ratios (r = 0.37-0.40). In girls, the relationship of ghrelin with the 2D:3D (r = 0.45) and 2D:4D (r = 0.48) finger ratios was significant. In boys, but not in girls, IGF-I (r = 0.42) and IGFBP-3 (r = 0.44) correlated only with the 2D:4D finger ratio. Leptin and insulin did not correlate with the finger-length ratios. In boys, the most important hormone to characterize several finger-length ratios was ghrelin (13.7-15.6% variance accounted for). Ghrelin and testosterone together accounted for 20.3% (R 2 × 100) of the variance in the 2D:4D ratio. In girls, estradiol was correlated with the 2D:3D ratio (25.7%) and estradiol in combination with ghrelin with the 2D:4D ratio (30.0%). In conclusion, ghrelin appears to be a further biochemical parameter in addition to the sex steroids which correlated with different digit-length ratios at least in boys.